2013
DOI: 10.4274/tdd.1349
|View full text |Cite
|
Sign up to set email alerts
|

The Retrospective Evaluation of Childhood Psoriasis Clinically and Demographic Features

Abstract: Objective: This study was aimed to define the clinical and demographic findings of psoriasis in childhood. Methods: In this retrospective study, the data from 64 children with psoriasis admitted at the our dermatology clinic between January 2007 and January 2011 were included whose data were fully. Results: Of the patients, 37 (57.8%) were boys and 27 (42.2%) were girls. Mean age of the children was 10.08 ±3.98 years (3-16). In 10 (15%) cases, a positive family history was detected. The most frequent localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
(35 reference statements)
5
6
0
Order By: Relevance
“…The study conducted in India revealed that 31% of the patients had nail involvement (10). As a result of the study conducted with pediatric patients in our country by Karadağ et al, nail involvement ratio was stated as 9% (4). In our study the nail involvement ratio was 18.57% (8 boys, 5 girls).…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The study conducted in India revealed that 31% of the patients had nail involvement (10). As a result of the study conducted with pediatric patients in our country by Karadağ et al, nail involvement ratio was stated as 9% (4). In our study the nail involvement ratio was 18.57% (8 boys, 5 girls).…”
Section: Discussionsupporting
confidence: 51%
“…Another study conducted in Australia with 1262 patients revealed this ratio as 71% (11). A study conducted by Karadağ et al in our country resulted in 10% family history ratio (4). In our study, the positive family history ratio was 31.4%.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations